Pedagogical, Technological, and Psychological Mediators on the English Language Teachers' Readiness for Asynchronous Online Teaching: A Systematic Review - Muhamad Rifqi Bakhtiar (Lingual: Journal of Language and Culture, 2025)
The rapid move to online education during and after the pandemic increased the use of learning management systems (LMS) for teaching and assessment. Yet, little is known about what helps English teachers feel ready to teach asynchronously with an LMS. This paper reports a systematic review that examined the pedagogical, technological, and psychological factors that mediate the link between LMS modality and teachers’ readiness to run online classes. Following PRISMA 2020, 29 published articles between 2019 and 2025 were screened, including three studies (one EFL systematic review and two teacher surveys was screened 29). The findings show three consistent mediators. First, pedagogical design matters: clear task structures, LMS-based assessment, and activities that support active learning improve teachers’ confidence to teach asynchronously. Second, technological support is essential: reliable access, useful LMS features, and ongoing training help teachers use platforms effectively. Third, psychological factors play a key role: teacher self-efficacy and positive attitudes toward technology are linked to higher readiness, while concerns about workload can reduce it. A meta-analysis was not conducted because the included studies did not report standardized quantitative data. The review recommends repeated, practice-focused professional development informed by TPACK, stronger LMS reliability and support services, and better reporting of effect sizes and sample details in future research so that pooled estimates can be produced.